Assessment of clinical significance of ultrasonographic detection ofhyperechogenic deposits in hyaline cartilage in patients with knee osteoarthritis - A. V. Petrov; N. V. Matveeva; A. A. Petrov (Научно-практическая ревматология)
The aim of the study was to assess the relationship between the detection of hyperechogenic deposits (HD) in the hyaline cartilage of the knee joints (KJ) at ultrasonography in patients with osteoarthritis (OA), clinical manifestations and structural changes according to KJ ultrasonography and radiography. Material and methods. A prospective analysis of clinical, radiological and ultrasonographic data of 114 patients with knee OA was conducted. The patients were divided into two groups: 32 patients with HD detected in at least one of the KJ, and 82 patients without HD; 32 patients of the 1st group and 34 patients of the 2nd group were observed for 2 years. A comparative assessment of initial clinical manifestations (WOMAC index), x-ray data and ultrasonographic parameters of the subchondral bone, hyaline cartilage and the degree of synovial inflammation in the groups of patients at the beginning of the study and after 2 years was carried out. The exclusion criteria were other joint diseases; paroxysmal course of the inflammatory process in KJ; trauma and history of operations on KJ; ESR >20 mm/h, uric acid level >360 μmol/l and C-reactive protein >5 mg/l. Results and discussion. HD in hyaline cartilage was found in 28.1% of patients with knee OA. After 2 years HD remained in all patients having them at inclusion, and in 5.6% of the patients they were found for the first time. In 13 patients with HD in hyaline cartilage, synovial fluid was studied and in all cases calcium pyrophosphate crystals were identified by phase-contrast microscopy. The presence of HD in the hyaline cartilage of patients with knee OA was accompanied by more pronounced ultrasonographic signs of synovitis and was associated with a higher rate of osteophytes growth in the absence of the changes of the hyaline cartilage thickness according to the ultrasonography and the width of the joint space according to x-ray. Conclusion. The presence of HD in the hyaline cartilage of patients with knee OA according to ultrasound examination may be associated with the deposition of calcium pyrophosphate crystals and is associated with persistent synovitis and accelerated growth of osteophytes.